P053 The intestinal complement system and its role in dysregulation of the intestinal B-cell compartment in Crohn's Disease patients. (21st January 2022) - Raschdorf, A; Preisker, S; Brethack, A K; Bokemeyer, A; Bettenworth, D; Sina, C; Derer, S
Abstract: Background: For several decades, there is growing evidence that a hyperactive B-cell compartment may be involved in the disturbed mucosal immune response in Crohn's disease (CD) patients. This is reflected by approximately one third of all CD patients displaying an excessive production of autoantibodies against the intestinal M-cell expressed FimH receptor glycoprotein 2 (GP2) which inhibits induction of adaptive immunity against adherent-invasive flagellated bacteria. However, underlying mechanisms of an imbalanced B-cell compartment in CD patients still remain elusive. Given that the complement system plays a critical role in the detection and clearance of bacteria and promotes B-cell immunity, we asked if the complement system contributes to a dysregulated B-cell response in CD. Methods: Systematical expression analyses of the intestinal complement components were performed in IBD patients, including CD and ulcerative colitis (UC) patients, versus non-IBD controls. Additionally, activity of the three activation pathways of complement system was studied in serum samples of CD patients and controls. Further, immunoglobulin levels in intestinal biopsies, sera and fecal samples were analyzed. Results: CD patients, but no UC patients, showed increased expression of the early classical complement pathway components C1QA, C1QB, C1S, C2, C3, C4A, CR1 and CR2 in sigmoidal biopsy samples that does not differ significantly between remission and active disease state. This could be verified by immunohistochemistry, displaying an over-representation of mucosal C1q, C3 and B-cell expressed CR2 (also CD21) in colon biopsies of CD patients in remission. In line with this, CD patients in remission present with enhanced activity of the classical as well as alternative pathway of complement activation in serum compared to non-IBD controls. Accordingly, high protein levels of C3 cleavage fragments were detected in fecal samples from CD patients in contrast to non-IBD controls. While there were no differences in systemic immunoglobulin levels in serum, intestinal IgM was increased in CD patients in remission. Notably, fecal IgA levels were strongly diminished in these patients, while expression of the polymeric immunoglobulin receptor was not affected. Conclusion: In summary, our findings demonstrate an augmented activation of the intestinal complement system that may potentially be involved in the etiology of CD. Expansion of mucosal IgM+/CR2+ B cells together with a reduced fecal IgA level, points to a locally disturbed induction of intestinal IgA secreting plasma cells in CD patients.